(untitled) (Boletín Epidemiológico Semanal, 2024)
Introduction: Epidemiological analysis of invasive pneumococcal disease (IPD) in Spain during 2023 and its comparison with previous years (2015-2022). Method: Descriptive epidemiological analysis of cases of IPD reported to the National Epidemiological Surveillance Network (RENAVE). The variables analysed were: sex, age, date of symptom onset, reporting region, death, clinical manifestation and serotype. Results: In 2023, 4,814 cases of IPD were reported in Spain, with an overall cumulative incidence rate per 100,000 inhabitants (IR) of 9.91 (12.16 in men and 7.74 in women). Incidence was highest in the <1-year group (IR of 29.97), followed by those ≥ 65 years (IR of 23.35) and by the 1-4-year group (IR of 23.32). In the <1 year and 1 to 4-year groups, 39.7% and 33.3%, respectively, were caused by serotypes included in PCV13. In the age group ≥65 years, 70.5% of IPDs were caused by a serotype included in PPV23. Vaccine serotypes 8 and 3 caused 41% of the IPDs in which the serotype was reported. Conclusions: AI increased in all age groups, reaching prepandemic IR. It is necessary to continue improving the quality of the information reported to RENAVE.